Evaluation of concentration and antiseptic effect of sodium hypochlorite in cattle foot bath - Silva, Luiz Antônio Franco da; Coelho, Karyne Oliveira; Damasceno, Adilson Donizeti; Nicolau, Edmar Soares; Andrade, Maria Auxiliadora; Fioravanti, Maria Clorinda Soares; Mesquita, Albenones José; Barbosa, Valessa Teixeira; Moura, Maria Ivete de (Semina: Ciências Agrárias, 2007)
This study aimed to evaluate the antiseptic effect of 2% and 4% sodium hypochloride solutions in footbath for bovines, considering parameters as stability during storage and use, action on mesophilic aerobic and anaerobic microorganisms and direct effects on tissue. Healthy bovines passed by a footbath, once a day, during five days. At the end of passages, samples of each solution were harvested for physiochemical and microbiological analysis. The first samples were obtained immediately after the solution deposition in footbath. Student t Test (p= 0,05%) was applied for data analysis. It was observed that 2% and 4% solutions didn't show significant differences on aerobic and anaerobic microorganisms counting, suggesting that solutions have the same antiseptic effect. In both solutions, the pH remained steady. Free chlorine concentrations showed levels equivalent to zero from the third day. Clinical signs of injury weren't observed in interdigital skin and others digital regions. Thus, these results allow us to conclude that sodium hypochloride solution in 2% and 4% dilutions, when they are used in footbath, have antiseptic effect in bovine digits, however, the renewal must be after 48 hours.